GAMBARAN DUKUNGAN KELUARGA TERHADAP PERUBAHAN KONSEP DIRI PASIEN PASCA STROKE DI POLI NEUROLOGI HANAFIAH BATUSANGKAR - Wati, Del Fatma; Yanti, Yusda (Universitas Fort De Kock Bukittinggi, 2018)
Stroke can affect all aspects of personal, social, physical, psychological, patients in doing something that is usually done before a stroke, so often show attitudes and behavior such as there is no hope and feel isolated. Initial survey of 5 patients after stroke, 2 people treated with other people because their families could not accompany, 3 people felt inferior in the environment because of their physical limitations. The purpose of this study was to describe the family support with changes in self-concept of post-stroke patients. The design of this study uses qualitative methods with the approach of phenomenology study. The number of participants of 8 people was taken by purposive technique according to the research criteria. Data collection methods in this study are in-depth interviews, and field notes. The study was carried out at the Hanafiah SM Batusangkar Neurology Poly in January 2018. Phases in the data analysis phenomenology study read interviews, summarize coding, analyze transcripts, return to participant texts, compare and distinguish, theme integration. This study produced two themes (1) Less attention (2) Self Acceptance. The results of this study can provide information for families in treating Post Stroke sufferers to changes in self-concept in order to increase their support while at home. Keywords: Family Support, Self Concept, Post Stroke, Self Acceptance